INCREASING THE 4th GRADE STUDENTS SCIENCE COMPETENCY THROUGH PROBLEM BASED LEARNING MODEL - Arnasari, Athalia; Hardini, Agustina Tyas Asri (Jurnal Pendidikan dan Pengajaran, 2017)
This research aims to improve student learning outcomes in natural sciences for grade 4, the second term of the academic year 2016/2017 at SD Negeri Mangunsari 02 Salatiga through the Problem Based Learning model. This classroom action research was conducted in two cycles. Subjects of this study are the fourth grade students of SD Negeri Mangunsari 02 Salatiga, consisted of 14 male students and 9 female students. Data collection was using non-test and test techniques.Â  Results show that in pre cycle condition, student who pass are 11 students (47.82%), i.e. 14 students in cycle I (60.86%), and 20 students (86.95%) in cycle II. The average score in pre cycle condition was 59.13, 68.73 in cycle I, and 75.04 cycle II.Â  Therefore, the application of Problem Based Learning model in lecturing science in the fourth grade of Mangunsari 02 Elementery School Salatiga, can improve the student learning activity.